Sporadic Cryptosporidium infection in Nigerian children: Risk factors with species identification - HOLLAND, CELIA; TANNER, COLBY (My University, 2011)
A cross-sectional study was conducted to investigate risk factors for sporadic Cryptosporidium infection in a paediatric population in Nigeria. Of 692 children, 134 (19?4%) were infected with Cryptosporidium oocysts. Cryptosporidium spp. were identified in 49 positive samples using PCR?restriction fragment length polymorphism and direct sequencing of the glycoprotein60 (GP60) gene. Generalized linear mixed-effects models were used to identify risk factors for all Cryptosporidium infections, as well as for C. hominis and C. parvum both together and separately. Risk factors identified for all Cryptosporidium infections included malaria infection and a lack of Ascaris infection. For C. hominis infections, stunting and younger age were highlighted as risk factors, while stunting and malaria infection were identified as risk factors for C. parvum infection.
PUBLISHED
Keywords: Infection; Immunology; Cryptosporidium; Nigeria; Immunology, Inflammation & Infection